Amelioration of excess collagen IαI, fibrosis, and smooth muscle growth in TNBS-induced colitis in IGF-I(+/−) mice - Mahavadi, Sunila (2010)
BACKGROUND & AIMS: Strictures occur in ~30% of patients with Crohn’s disease and are characterized by intestinal smooth muscle hyperplasia, hypertrophy, and fibrosis due to excess extracellular matrix production including collagen. Insulin-like Growth Factor-I (IGF-I) expression is increased in smooth muscle cells of the muscularis propria in Crohn’s disease and in animal models of Crohn’s disease, including TNBS-induced colitis. While upregulated IGF-I is conjectured to cause smooth muscle cell growth and collagen production in the inflamed intestine, its role in the development of fibrosis has not been directly demonstrated. METHODS: Colitis was induced in IGF-I(+/−) or wildtype C57BL/6J mice by rectal administration of TNBS or ethanol vehicle. After 7 days colonic smooth muscle cells were isolated and used to prepare RNA or protein lysates. Transcript levels of IGF-IEa, IGF binding protein (IGFBP)-3, IGFBP-5, TGF-β1 and collagen IαI were measured by quantitative RT-PCR. Corresponding protein levels were measured by western blot or ELISA. Fibrosis was measured using digital image analysis of Masson’s-trichrome stained histologic sections. RESULTS: In IGF-I(+/−) mice, which express significantly lower levels of IGF-I than wildtype, the response to TNBS-induced colitis: upregulation of IGF-I, IGFBP-3, IGFBP-5, and collagen IαI expression, the resulting collagen deposition, and fibrosis are all significantly diminished compared to C57BL/6J wildtype controls. TGF-β1 expression and its increase following TNBS administration are not altered in IGF-I(+/−) mice compared to wildtype. CONCLUSIONS: The findings indicate IGF-I is a key regulator in intestinal smooth muscle of smooth hyperplasia and excess collagen production that leads to fibrosis and longterm to stricture formation.